Sanksi Tindakan Dalam Hukum Pidana di Indonesia Perspektif Teori Relatif - Uni Sabadina (UIR Press, 2025)
Abstract: This study aims to analyze the position and regulation of action sanctions (maatregel) in the Indonesian criminal law system from the perspective of Relative Criminal Theory. The research method used is normative juridical through literature studies of laws and regulations and legal literature. The results of the study show that although theoretically Indonesia's criminal law adheres to a double track system that places criminal sanctions (straf) and equivalent action sanctions, in the practice of legislation and law enforcement, action sanctions are still positioned as number two and are less accommodated. Traditional criminal sanctions (such as imprisonment) remain the